cGAS-STING signaling: a therapeutic target in inflammatory bowel disease and related colorectal cancer - Chen, Xi; Tang, Xiaohua; Chen, Sixuan; Ye, Yang; Mao, Fei (Frontiers in Immunology, 2026)
The cyclic GMP-AMP synthase (cGAS)-stimulator of interferon genes (STING) signaling pathway is a critical mechanism of DNA sensing in innate immunity. Activation of this pathway can induce the production of interferons and proinflammatory cytokines. In the intestine, this pathway exhibits bidirectional regulatory properties, with appropriate activation maintaining homeostasis and inhibiting tumorigenesis, while excessive activation leads to inflammatory responses. A thorough exploration of the molecular mechanisms and regulatory networks of the cGAS-STING signaling pathway offers a significant theoretical foundation and potential treatment targets for developing novel strategies to treat intestinal diseases. This review summarizes the most recent developments on the function of the cGAS-STING regulatory pathway in colorectal tumors and inflammatory bowel disease. It discusses targeted therapeutic approaches that interfere with this pathway.